Temporal patterns of pre-competition mood states and state anxiety among UiTM athletes / Bita Mehdipoor Keikha - Mehdipoor Keikha, Bita (2015)
The aims of this study are to examine the differences of three state anxiety components and six mood state sub-scales between team and individual sports among UiTM University student athletes in different temporal patterns prior to MASUM 2011 competition. The participants comprised of 219 male and female athletes ranging from 18 to 26 years old. The questionnaires were distributed to the participants within three time frames (one week, one day and an hour) prior to competition. Stratified sampling technique was employed in this study. Competitive State Anxiety Inventory2 (CSAI-2) and Profile of Mood States- Adolescence (POMS-A) were used to measure state anxiety and mood states. All measurements were made at three different temporal patterns: one week, one day and one hour prior to competitions. The results were analyzed using two way repeated measure ANOVA (between-within subject ANOVA). The Statistical Package for Social Science (SPSS) version (21) was used to analyze the results. The differences between anxiety components and mood state subscales in team and individual sports in different temporal patterns were significant. Differences were also found between different type of sports in mood states and state anxiety sub-scales scores. However, no significant relation was found between result of the competition and mood states and state anxiety sub-scales scores.